2009
DOI: 10.1007/s11204-010-9074-8
|View full text |Cite
|
Sign up to set email alerts
|

In-situ measurements of pile-to-pile load distribution in foundations

Abstract: In analyzing a slab raft connected to a group or field of piles, it is important to determine the computed resistance and flexibility of the piles. The performance of a separately embedded pile (single pile) differs from that of a pile acting as a component part of a simultaneously embedded pile group. Here, the character of the work performed by the pile will depend on its positioning (edge, corner, frontal, or interior) within the group.According to Mandolini et al.[1], investigations associated with the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…This has been attributed to the fact that the piles at the corners have limited mobility due to a smaller settlement on the sides, which leads to elevated compressive loads on side piles. In addition, the formula has been applied to a case study by Shulyat'ev, and Kharichkin, 2009. The application steps of the formula have been explained in details.…”
Section: Sonuçlar Ve Tartışmamentioning
confidence: 99%
See 2 more Smart Citations
“…This has been attributed to the fact that the piles at the corners have limited mobility due to a smaller settlement on the sides, which leads to elevated compressive loads on side piles. In addition, the formula has been applied to a case study by Shulyat'ev, and Kharichkin, 2009. The application steps of the formula have been explained in details.…”
Section: Sonuçlar Ve Tartışmamentioning
confidence: 99%
“…In addition, the formula has been applied to a case study by Shulyat'ev, and Kharichkin, 2009. The application steps of the formula have been explained in details.…”
Section: Extended Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…De Sanctis and Russo [6] found load increases in the corner piles of circular tanks. Likewise, Shulyat'ev and Kharichkin [7] reported that the corner and center piles of the building in Moscow's Pavshinsk River Valley did not carry an equal pile load. Researchers gave q cor /q cen as 2.4 for the foundation of a building resting on alluvial soil by the river.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one of the cases, the pile cap carried about 40% of the total axial load at the end of construction, and this percentage had decreased to below 25% by the end of the monitoring. Shulyat’ev and Kharichkin ( 4 ) measured the load distribution between six representative piles in a large pile group supporting a high-rise building with strain gauges installed on the pile heads. Yamashita et al ( 5 ) studied the load sharing between the piles and the pile cap (raft) of piled raft foundations for seven high-rise buildings during and after the completion of the construction.…”
mentioning
confidence: 99%